The influence of corporate governance on firm value: a case study in Indonesian manufacturing industries - Werner Ria Murhadi (Universitas Negeri Surabaya, 2021)
This study aims to determine the effect of corporate governance on financial performance and financial performance on dividend policy, then examining the effect of financial performance and dividend policy on firm value. The research approach is quantitative with panel data type. The sample are companies listed in the manufacturing industries on the Indonesia Stock Exchange. This study found that independent commissioners' existence does not affect financial performance. The size of the board of commissioners, audit committee members, and the number of board meetings do not affect financial performance. The study also found that financial performance and free cash flow affect the company's dividend policy. Finally, the results show that financial performance affects firm value while dividend policy does not affect it. These results have theoretical implications for supporting agency theory. The independent commissioners will reduce conflict and thus improve the financial performance.